Survival after laparoscopic and open surgery for colon cancer: a comparative, single-institution study - Cianchi, Fabio (BMC Surg, 2015)
BACKGROUND: Some recent studies have suggested that laparoscopic surgery for colorectal cancer may provide a potential survival advantage when compared with open surgery. This study aimed to compare cancer-related survivals of patients who underwent laparoscopic or open resection of colon cancer in the same, high volume tertiary center. METHODS: Patients who had undergone elective open or laparoscopic surgery for colon cancer between January 2002 and December 2010 were analyzed. A clinical database was prospectively compiled. Survival analysis was calculated by using the Kaplan-Meier method. RESULTS: A total of 460 resections were performed. There were no significant differences between the laparoscopic (n = 227) and the open group (n = 233) apart from tumor stage: stage I tumors were more frequent in the laparoscopic group whereas stage II tumors were more frequent in the open group. The mean number of harvested lymph nodes was significantly higher in the laparoscopic than in the open group (20.0 ± 0.7 vs 14.2 ± 0.5, P < 0.01). The 5-year cancer-related survival for patients undergoing laparoscopic resection was significantly higher than that following open resections (83.1% vs 68.5%, P = 0.01). By performing a stage-to-stage comparison, we found that the improvement in survival in the laparoscopic group occurred mainly in patients with stage II tumors. CONCLUSIONS: Our study shows a survival advantage for patients who had undergone laparoscopic surgery for stage II colon cancer. This may be correlated with a higher number of harvested lymph nodes and thus a better stage stratification of these patients.